2020
DOI: 10.1161/circresaha.119.316260
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive In Vivo Assessment of Cardiac Metabolism in the Healthy and Diabetic Human Heart Using Hyperpolarized 13 C MRI

Abstract: Rationale: The recent development of hyperpolarized 13 C magnetic resonance spectroscopy has made it possible to measure cellular metabolism in vivo, in real time. Objective: By comparing participants with and without type 2 diabetes mellitus (T2DM), we report the first case-control study to use this technique to record changes in cardiac metabolism in the healthy and diseased human heart. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
189
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(195 citation statements)
references
References 47 publications
4
189
2
Order By: Relevance
“…This switch in fuel utilization towards more oxygene cient glucose metabolism may account for the improved recovery post-ischemia. Given the recent demonstration of the ability of hyperpolarized magnetic resonance to study alterations in metabolism in the human heart [44,45], there is clear potential for such studies to be translated into clinical trials assessing the potential for metabolic therapies in the diabetic heart.…”
Section: Resultsmentioning
confidence: 99%
“…This switch in fuel utilization towards more oxygene cient glucose metabolism may account for the improved recovery post-ischemia. Given the recent demonstration of the ability of hyperpolarized magnetic resonance to study alterations in metabolism in the human heart [44,45], there is clear potential for such studies to be translated into clinical trials assessing the potential for metabolic therapies in the diabetic heart.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to image metabolism has driven its lead in the clinical translation. Recently, the first human study of cardiac disease found impaired myocardial energetics with [1-13 C]pyruvate in diabetic patients (47). Of interest to pH-imaging, they were able to detect carbon dioxide in their spectra.…”
Section: Discussionmentioning
confidence: 99%
“…While the safety and feasibility of using hyperpolarized [1- 13 C]pyruvate as a tool to interrogate cellular metabolism has been demonstrated in many studies in humans (2,6,7,(13)(14)(15)(16), hyperpolarized [1-13 C]lactate represents an alternative for probing cardiac PDH flux with less perturbation of the metabolic state. At the 0.1 mmol/kg dose that has been utilized in all the human hyperpolarized [1-13 C]pyruvate studies to date, the injected substrate concentration (~2 mM after dilution by blood) would greatly exceed its endogenous blood concentration (17).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated in small and large animal models that HP MRI can be used to probe changes in cardiac metabolism due to modulation in substrate availability as well as cardiac diseases (3)(4)(5). The feasibility of studying cardiac metabolism in the human heart has also been shown recently (6,7). In all the hyperpolarized metabolic imaging studies performed so far, [1- 13 C]pyruvate is the most commonly used substrate due to the high achievable polarization, long T1 relaxation time, and the important role of pyruvate in cellular metabolism.…”
Section: Introductionmentioning
confidence: 99%